Italian nominees for the Nobel Prize in physiology or medicine 1901-1950: Scholars, Research trends, Hotspots. - Padrini, Giacomo; Borghi, Luca; Hansson, Nils (Medicina Historica, 2022)
As the Nobel Prize is considered to be the most prestigious award in the world, it is not surprising that already much has been written about it. Whilst the majority of studies have focused on the laureates, this article sheds light on the much larger group of nominees for the Nobel Prize in physiology or medicine in Italy during the first half of the 20th Century. Drawing on information from the Nobel archives and secondary literature this article reconstructs some structures behind the nominations including popular research topics, cities and nominators. We found candidates to pool in few cities and identified infectious diseases as a prevalent research topic among the nominees during the examined time period. Having found the vast majority of nominations to originate in Italy with nominator and nominee often holding positions in the same university, this study also discusses factors that might have influenced the choice of the nominators without necessarily being related to the work of the nominee itself.